2015
DOI: 10.3109/08977194.2015.1076406
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-326 is associated with poor prognosis and promotes growth and metastasis by targeting FSCN1 in gastric cancer

Abstract: Our study demonstrated that miR-326 overexpression was a poor prognostic marker for gastric cancer patients, and miR-326 served as a tumor suppressor in gastric cancer via directly regulating FSCN1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 25 publications
4
51
0
Order By: Relevance
“…miR-326 downregulation is correlated with clinical stage, tumour depth, lymph node metastasis and distant metastasis. Survival analysis indicated that miR-326 is a poor independent prognostic factor for patients with gastric cancer (36). In another study, miR-326 was decreased in osteosarcoma, and low miR-326 expression is associated with distant metastasis and advanced clinical stage.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…miR-326 downregulation is correlated with clinical stage, tumour depth, lymph node metastasis and distant metastasis. Survival analysis indicated that miR-326 is a poor independent prognostic factor for patients with gastric cancer (36). In another study, miR-326 was decreased in osteosarcoma, and low miR-326 expression is associated with distant metastasis and advanced clinical stage.…”
Section: Discussionmentioning
confidence: 94%
“…Low miR-326 expression is strongly correlated with advanced pathological grade and low KPS score (35). Li et al reported that miR-326 is downregulated in gastric cancer and cell lines (36,37). miR-326 downregulation is correlated with clinical stage, tumour depth, lymph node metastasis and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ji et al identified that miR-326 inhibited GC cell growth by downregulating NOB1 [20]. Li et al demonstrated that downregulation of miR-326 was associated with poor prognosis and promoted GC growth [21]. To further verify the relationship between hsa_circ_0000467 and miR-326-3p in GC, we performed rescue experiments using different groups of BGC-823 and SGC-7901 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al, 2010), prostate cancer (H. Kristensen et al, 2016), esophageal cancer (Hong et al, 2014), cutaneous T-cell lymphoma (CTCL; Ralfkiaer et al, 2011), gastric cancer (Y. Li, Gao, Xu, Ma, & Yang, 2015), pancreatic ductal adenocarcinoma (Z. L. , hepatocellular carcinoma (HCC; Hu, Ran, Chen, Zhang, & Xu, 2017), medulloblastoma (Ferretti et al, 2008), acute myelogenous leukemia (Koutova et al, 2015), and chronic myelogenous leukemia (CML; Babashah et al, 2013). miR-326 is also involved in the pathogenesis of idiopathic pulmonary fibrosis (Das et al, 2014), and HIV infection (Houzet et al, 2012).…”
Section: Mir-326 In Other Diseasesmentioning
confidence: 99%